Plastics and the Environment - Harrison, R. M.; Hester, R. E. (Royal Society of Chemistry, 2019)
Plastic has become a ubiquitous part of modern life. A cheap, lightweight material, it is used in everything from food packaging to consumer electronics and microbeads in cosmetic products. However, we are becoming increasingly aware of the problems our reliance on plastic is causing in the environment. For example, recent campaigns have highlighted the build-up of microbeads in the marine environment and the damage this is doing to wildlife, and the problem of marine litter, often in very remote locations. There are also concerns over exposure to plasticisers and their possible consequences for health. The plastics industry is under increasing pressure, not only from the government and environmental groups, but also from consumers, to improve the environmental impact of their products. This book presents an introduction to the uses of plastics and an overview of how they interact with the environment. It is a valuable resource for students studying environmental science as well as researchers working in the plastics industry, and policy makers and regulators concerned with waste disposal and environmental planning and conservation.
Keywords: Plastics -- Environmental aspects.; elektronické knihy; electronic books